1998
DOI: 10.1029/98jd00345
|View full text |Cite
|
Sign up to set email alerts
|

Apparent breakdown of reciprocity in reflected solar radiances

Abstract: Abstract.Observations of reflected solar radiation measurements from natural surfac• (e.g., clouds and forested biomes) are often noted as disobeying the principle of reciprocity. In these contexts the application of reciprocity has been in its directional form. We note that the general principle of reciprocity also encompasses spatial attributes and reduces to a directional form only when the areas of illumination and measurement are the same. In either form a proper reciprocal set of reflected solar radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…This violation of reciprocity is a desirable attribute of stochastic RT modeling at least in atmospheric applications. It is indeed consistent with realworld satellite observations of reciprocity violation uncovered by DiGirolamo et al [61] in spatially variable cloud scenes inside a relatively broad field of view, and readily replicated with numerical Monte Carlo simulations. These findings were soon explained theoretically by Leroy [62].…”
Section: Single Scattering In D = 3: Violation Of Angular Reciprocitysupporting
confidence: 87%
“…This violation of reciprocity is a desirable attribute of stochastic RT modeling at least in atmospheric applications. It is indeed consistent with realworld satellite observations of reciprocity violation uncovered by DiGirolamo et al [61] in spatially variable cloud scenes inside a relatively broad field of view, and readily replicated with numerical Monte Carlo simulations. These findings were soon explained theoretically by Leroy [62].…”
Section: Single Scattering In D = 3: Violation Of Angular Reciprocitysupporting
confidence: 87%
“…an out of focus image) the scene appears to behave more like a plane parallel one. Analogous resolutiondependent effects were noted earlier by Di Girolamo et al [1998] and by Oreopoulos and Davies [1998].…”
Section: Discussionsupporting
confidence: 84%
“…In conclusion, this paper presents a theoretical framework for understanding and quantifying deviations from directional reciprocity. The predictions of (14) agree a posteriori with the results of Monte Carlo simulations [Di Girolamo et al, 1998], which showed that the deviations from reciprocity (1) increase with scene heterogeneity, (2) increase as the view direction gets farther from the illumination direction, (3) decrease as the sensor pixel size increases. The scaling derived from the theory permits to determine whether angular models should be considered as reciprocal or not, depending on the characteristics of photon mean free path, sensor resolution, and scene heterogeneity of the physical problem to be studied.…”
Section: Discussionsupporting
confidence: 72%